A novel Actinidia cytorhabdovirus characterized using genomic and viral protein interaction features. (20th July 2021) - Wang, Yanxiang; Wang, Guoping; Bai, Jianyu; Zhang, Yongle; Wang, Ying; Wen, Shaohua; Li, Liu; Yang, Zuokun; Hong, Ni
Abstract: A novel cytorhabdovirus, tentatively named Actinidia virus D (AcVD), was identified from kiwifruit ( Actinidia chinensis ) in China using high‐throughput sequencing technology. The genome of AcVD consists of 13, 589 nucleotides and is organized into seven open reading frames (ORFs) in its antisense strand, coding for proteins in the order N‐P‐P3‐M‐G‐P6‐L. The ORFs were flanked by a 3′ leader sequence and a 5′ trailer sequence and are separated by conserved intergenic junctions. The genome sequence of AcVD was 44.6%–51.5% identical to those of reported cytorhabdoviruses. The proteins encoded by AcVD shared the highest sequence identities, ranging from 27.3% (P6) to 44.5% (L), with the respective proteins encoded by reported cytorhabdoviruses. Phylogenetic analysis revealed that AcVD clustered together with the cytorhabdovirus Wuhan insect virus 4. The subcellular locations of the viral proteins N, P, P3, M, G, and P6 in epidermal cells of Nicotiana benthamiana leaves were determined. The M protein of AcVD uniquely formed filament structures and was associated with microtubules. Bimolecular fluorescence complementation assays showed that three proteins, N, P, and M, self‐interact, protein N plays a role in the formation of cytoplasm viroplasm, and protein M recruits N, P, P3, and G to microtubules. In addition, numerous paired proteins interact in the nucleus. This study presents the first evidence of a cytorhabdovirus infecting kiwifruit plants and full location and interaction maps to gain insight into viral protein functions. Abstract : The complete genome of a novel cytorhabdovirus, Actinidia virus D, was sequenced. We report for the first time that the rhabdovirus M protein shows unique microtubule localization and recruits N, P, P3, and G to microtubules.